2016 Eighth International Conference on Quality of Multimedia Experience (QoMEX) 2016
DOI: 10.1109/qomex.2016.7498949
|View full text |Cite
|
Sign up to set email alerts
|

Free viewpoint video quality assessment based on morphological multiscale metrics

Abstract: In this paper, two image quality metrics based on morphological multiscale decompositions have been applied for the evaluation of free viewpoint video sequences. These sequences are synthesized using decompressed depth maps in the Depth-Image-Based Rendering synthesis process. Since the synthesis introduces edge distortion in the synthesized image/video, morphological filters are used for their ability to maintain important geometric information (i.e., edges) across different resolution levels. The edges displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Constructed in two ways as morphological low‐pass pyramid and morphological band‐pass pyramid, it uses morphological filters to decompose the image. Most of the pyramid schemes are based on the usage of linear filters but research has been done in [7, 11] to investigate the role and scope of non‐linear filtering in pyramid construction. It has also been suggested that linear filter‐based pyramid construction techniques manipulate and change the intensities of the objects hence, consequently the location of contours and edges also changes.…”
Section: State‐of‐the‐artmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructed in two ways as morphological low‐pass pyramid and morphological band‐pass pyramid, it uses morphological filters to decompose the image. Most of the pyramid schemes are based on the usage of linear filters but research has been done in [7, 11] to investigate the role and scope of non‐linear filtering in pyramid construction. It has also been suggested that linear filter‐based pyramid construction techniques manipulate and change the intensities of the objects hence, consequently the location of contours and edges also changes.…”
Section: State‐of‐the‐artmentioning
confidence: 99%
“…Erosion removes comparatively brighter regions, which are smaller than the considered structuring element. The dilation operation afterwards ensures that the original size of the brighter regions greater than the structuring element is retained [11]. A general morphological pyramid‐based decomposition process is shown in Fig.…”
Section: State‐of‐the‐artmentioning
confidence: 99%
“…Some of them consider common distortions [5] such as gaussian blur, additive noise, etc. Some publicly available datasets consider LF specific distortions [6] [7][8] such as compression, view synthesis related distortions. There is still a need for datasets who offers acquisition and display related distortions with the corresponding subjective scores.…”
Section: Light Field Related Distortionsmentioning
confidence: 99%
“…In Free Viewpoint Video dataset(FVV) [6], seven different compression algorithms have been used to code depth maps. Coded depth maps are used to synthesize intermediate views to generate horizontal parallax videos with 50 frames.…”
Section: Light Field Related Distortionsmentioning
confidence: 99%
See 1 more Smart Citation